The importance of labor relations in ensuring self-employment of the population - Nizametdinov Ali Akramovich (THE INNOVATION ECONOMY, 2026)
This article examines the problems faced by self-employed individuals, including insufficient legal protection in labor relations, disputes with clients regarding the quality of services, and the lack of social insurance and pension payments. It analyzes how labor contracts or similar models can strengthen the legal protection of the self-employed, formalize their activities, and assess the share of the informal sector in the economy.